16th International Conference on Applications of Fuzzy Systems, Soft Computing and Artificial Intelligence Tools – ICAFS-2023 Volume 2 - Aliev, Rafik A.; Kacprzyk, Janusz; Pedrycz, Witold; Jamshidi, Mo; Babanli, M.B; Sadikoglu, Fahreddin M. (Lecture Notes in Networks and Systems, 2025)
XV, 380 p. 138 illus., 90 illus. in color.